KADAR ZAT GIZI DALAM ONCOM - Dewi Sabita Slamet; Ignatius Tarwotjo (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 1971)
Kadar zat gizi dalam ontjom. (The nutrient content of "ontjom"). Two kinds of "ontjom" were analyzed for their nutrient composition. In one, peanut presscake, and in the other residue left in the manufacture of soybean curd (tofu), was the basic material. Both were fermented with molds. The first type is known as "ontjom hitam" (black ontjom), the other is called "ontjom merah"  (red ontjom). Samples were bought in three markets in the city of Bogor. The average composition was as follows. Black ontjom: moisture 77.1 gc/c, ash 1.4 g%, protein 8.6 g%, fat 3.6 g% and iron 55.7 mg%. Red ontjom: moisture 80.7 g%, ash 0.8 g%, protein 4.9 g%, fat 2.3 g% and iron 9.6 mg%. Tulisan ini mengutarakan hasil analisa dua jenis oncom yang diperoleh dari tiga pasar di kota Bogor, dengan maksud melengkapi data yang pernah dikumpulkan, dan kemudian dapat menjadi bahan guna penyempurnaan Daftar Komposisi Bahan Makanan Indonesia.